2017
DOI: 10.46586/tosc.v2017.i2.228-249
|View full text |Cite
|
Sign up to set email alerts
|

Differentially 4-Uniform Permutations with the Best Known Nonlinearity from Butterflies

Abstract: Many block ciphers use permutations defined over the finite field F22k with low differential uniformity, high nonlinearity, and high algebraic degree to provide confusion. Due to the lack of knowledge about the existence of almost perfect nonlinear (APN) permutations over F22k, which have lowest possible differential uniformity, when k > 3, constructions of differentially 4-uniform permutations are usually considered. However, it is also very difficult to construct such permutations together with high nonli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 20 publications
1
5
0
1
Order By: Relevance
“…Remark 1. Theorem 1 complements previous work [9,12,18] on butterfly structure and gives rise to the sixth family of 4-uniform BCT permutations in even dimension. It was known from [18] that the closed butterfly V R in Theorem 1 possesses the best known nonlinearity when β = α + 1.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Remark 1. Theorem 1 complements previous work [9,12,18] on butterfly structure and gives rise to the sixth family of 4-uniform BCT permutations in even dimension. It was known from [18] that the closed butterfly V R in Theorem 1 possesses the best known nonlinearity when β = α + 1.…”
Section: Introductionsupporting
confidence: 78%
“…Let m, k be positive integers such that m is odd and gcd(k, m) = 1. Extending previous work [9,12], Li, Tian, Yu and Wang [18] considered a general bivariate polynomial R(x, y) of the form R(x, y) = (x + αy) 2 k +1 + βy 2 k +1 for any α, β ∈ F 2 m and proved that the corresponding butterflies H R and V R are differentially 4-uniform and have the best known nonlinearity when β = (α + 1) 2 k +1 . Under this condition, however, the closed butterfly V R may not be a permutation.…”
Section: Introductionmentioning
confidence: 55%
“…Unlike Dillon's original permutation, this bivariate structure can easily be defined using larger fields F 2 n as long as n is odd. It was also shown to always be at most differentially 4-uniform in [24], and follow-up works showed that further generalizations had the same property along with the best known nonlinearity [12,19,21]. Being an infinite family containing Dillon's permutation, there was of course hope that it might yield a solution to the big APN problem, but unfortunately it was later proved that it is impossible for a generalized butterfly to be APN unless it operates on 6 bits [14].…”
Section: Introductionmentioning
confidence: 99%
“…Подстановки являются составной частью таких современных криптографических примитивов, как блочные шифры, хэш-функции и некоторые поточные шифры. В последние годы появляются все новые способы построения подстановок с низкой дифференциальной равномерностью, высокой алгебраической степенью нелинейности и высокой нелинейностью [1][2][3][4][5]. Большая часть этих работ посвящена способам построения новых классов подстановок на основе имеющихся, в частности с использованием подстановок меньшей размерности.…”
Section: Introductionunclassified